2021
DOI: 10.1097/pq9.0000000000000436
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Discharge Medication Reconciliation Errors at 2 Pediatric Hospitals

Abstract: Introduction: Medication reconciliation errors (MREs) are common and can lead to significant patient harm. Quality improvement efforts to identify and reduce these errors typically rely on resource-intensive chart reviews or adverse event reporting. Quantifying these errors hospital-wide is complicated and rarely done. The purpose of this study is to define a set of 6 MREs that can be easily identified across an entire healthcare organization and report their prevalence at 2 pediatric hospitals. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Finally, this study adds to a nascent body of literature around free-text prescribing 5,6 . We found that the majority of medications prescribed using this method were common medications that could easily be prescribed using the structured fields in the EHR, and likely are perpetuated by poorly constructed user preference lists.…”
Section: Accepted Manuscriptmentioning
confidence: 89%
See 3 more Smart Citations
“…Finally, this study adds to a nascent body of literature around free-text prescribing 5,6 . We found that the majority of medications prescribed using this method were common medications that could easily be prescribed using the structured fields in the EHR, and likely are perpetuated by poorly constructed user preference lists.…”
Section: Accepted Manuscriptmentioning
confidence: 89%
“…We define a provider as any clinician capable of signing a medication order, which in this instance includes pharmacists, advanced practice providers, and physicians. Supplies, insulins, unlisted medications and investigational drug prescription records were excluded from triggering the alert as these were deemed appropriate for use of the free-text method 6 . Providers were pseudo-randomly assigned to either the visible alert (intervention) or silent alert (control) group based on their EHR user ID.…”
Section: Interventionmentioning
confidence: 99%
See 2 more Smart Citations
“…This method proves the importance of utilizing pharmacists in the admission medication reconciliation process and adds clarity to the scale and severity of medication errors that has been previously difficult and cumbersome to measure and convey [ 25 , 26 ]. A potential next step is to apply this method into a real-time or near real-time dashboard that would easily and quickly convey the findings of pharmacist-mediated medication reconciliation to hospital quality staff and leadership.…”
Section: Discussionmentioning
confidence: 99%